Dynamics of drop impact on solid surface: experiments and VOF simulations - Gunjal, P. R.; Ranade, V. V.; Chaudhari, Raghunath V. (AICHE Journal, 2005)
The process of spreading/recoiling of a liquid drop after collision with a flat solid surface was experimentally, and computationally studied to identify the key issues in spreading of a liquid drop oil a solid surface. The long-term objective of this study is to gain an insight in the phenomenon of wetting of solid particles in the trickle-bed reactors. Interaction of a falling liquid drop with a solid surface (impact, spreading, recoiling, and bouncing) was studied using a high-speed digital camera. Experimental data oil dynamics of a drop impact on flat surfaces (glass and Teflon) are reported over a range of Reynolds numbers (550-2500) and Weber numbers (2-20). A computational fluid dynamics (CFD) model, based on the volume of fluid (VOF) approach, was used to simulate drop dynamics on the flat sufaces. The experimental results were compared with the CFD simulations. Simulations showed reasonably good agreement with the experimental data. A VOF-based computational model was able to capture key features of the interaction of a liquid drop with solid surfaces. The CFD simulations provide information about finer details of drop interaction with the solid surface. Information about gas-liquid and liquid-solid drag obtained from VOF simulations would be useful for CFD modeling of trickle-bed reactors. (C) 2004 American Institute of Chemical Engineers.
Keywords: CFD; drop impact; recoiling; spreading; trickle bed; VOF